DEVELOPING CRITICAL CULTURE AWARNESS IN FOREIGN LANGUAGE CLASSROOM FOR COMMUNICATIVE EFFECTIVENESS - Normalela Normalela; Meilanie Zohra (English Language Teaching and Research, 2018)
As the dramatic technology changes, interconnected community from different national, ethnic, and religious cultural background is something that cannot be refuse in this globalization era.  The question appeared by the phenomenal is what happens when people from different cultures interact between one another? The answer is of course there is a big possibility that the thing such as cross-cultural probelms will appear.  As students who learn English as their foreign language, this kind of problem is something that will be faced by them.  Therefore, how to understand the culture of the native language is a salient thing to do in order to achieve the goal of the communication.  Unfortunately, many teachers are not careful on this kind of thing and they just focus on teach the pattern of the language.  As a resutl, students will have a problem when they got to do the communication with the English native speakers.  Increasing critical culture awarness is the solution to overcome this problem where this is aslo a major trend in EFL field nowadays.  As Byram mentions why students should learn the culture of the target language is because the foreign learner should know the culture of the society in which the language is spoken.  Hence, the objective of this paper is to propose the development of critical cultural awarness for the effectiveness of communication. Key words: Critical Culture Awarness, Foreign Learner, Communicative Effectiveness